Individual differences in Zhong-Yong tendency and processing capacity - Chang, Ting-Yun; Yang, Cheng-Ta (Frontiers in Psychology, 2014)
The present study investigated how an individual’s Zhong-Yong tendency is related to his/her perceptual processing capacity. In two experiments, participants completed a Zhong-Yong Thinking Style Scale and performed a redundant-target detection task. Processing capacity was assessed with a nonparametric approach (systems factorial technology, SFT) and a parametric (linear ballistic accumulator model, LBA) approach. Results converged to suggest a positive correlation between Zhong-Yong tendency and processing capacity. High middle-way thinkers had larger processing capacity in multiple-signal processing compared with low middle-way thinkers, indicating that they processed information more efficiently and in an integrated fashion. Zhong-Yong tendency positively correlates with the processing capacity. These findings suggest that the individual differences in processing capacity can account for the reasons why high middle-way thinkers tend to adopt a global and flexible processing strategy to deal with the external world. Furthermore, the influence of culturally dictated thinking style on cognition can be revealed in a perception task.